ANALISIS AKUNTABILITAS DAN SPIP TERHADAP PENGELOLAAN DANA DESA (DD) DALAM UPAYA MENINGKATKAN PEMBANGUNAN DI DESA GLURANPLOSO TAHUN 2022 - Dita Khoiriyah Ulfa; Yogie Surya D (Jurnal Ekonomi, Bisnis dan Social, 2024)
: This recearch aims to analyze Accountability and SPIP for the management of Village Funds (DD) in Gluranploso Village in 2022. The data collection method in the research is by using interview guidelines and documentation. This research uses qualitative research, where data collection uses primary data obtained directly from original sources, namely interviews with the informants concerned and secondary data obtained with evidence, notes, archives through documentation from the Gluranploso Village Goverment. Based on the results of the research that has been carried out, it can be seen that the accountability of Village Fund management in improving development in Gluranploso Village has not run optimally in terms of program accountability. This is because in 2022 the Gluranploso Village Goverment will focus Village Funds on the economic recovery process, so that resulting in delays in construction that year. The implementation of SPIP in Gluranploso Village has gone well in accordance with PP No. 60 of 2008.